Decreased Serum Maresin 1 Concentration Is Associated With Postmenopausal Osteoporosis: A Cross-Sectional Study - Wu, Jing; Li, Xin-Yue; Fang, Xia; Teng, Fang-Yuan; Xu, Yong (Frontiers in Medicine, 2022)
Background: Maresin 1 plays a role in the regulation of inflammation and metabolic diseases in vivo. An increasing number of studies have reported that postmenopausal osteoporosis (PMOP) is associated with inflammation. However, the potential relationship between the serum Maresin 1 content and PMOP is unclear. Aims: (1) To evaluate the Maresin 1 content in postmenopausal women with osteopenia, osteoporosis, or without these conditions (normal group) and (2) to analyze the correlations between Maresin 1 concentrations and bone mineral density (BMD) and bone turnover markers. Methods: In this cross-sectional study, we measured serum Maresin 1 concentrations, serum biochemical parameters, markers of bone metabolism, and BMD of the femoral neck, lumbar spine, and hip in 141 postmenopausal women. Results: We found that serum Maresin 1 in the osteopenia (140.09 ± 30.54 ng/ml) and PMOP (124.68 ± 31.35 ng/ml) groups were significantly lower than those in the normal group (167.38 ± 24.85 ng/ml) (P < 0.05 and P < 0.001). Serum Maresin 1 levels were positively correlated with femoral neck, lumbar spine, and hip BMD (P < 0.001). Meanwhile, Maresin 1 concentrations were positively associated with 25-hydroxyvitamin D (25(OH)D) levels (P < 0.001), but negatively correlated with β-CrossLaps of type 1 collagen containing cross-linked C-telopeptide (β-CTX) (P = 0.002), procollagen type I amino-terminal propeptide (PINP) (P = 0.004), tartrate-resistant acid phosphatase 5b (TRAP-5b) (P = 0.005), and osteocalcin (OC) levels (P = 0.001). Multivariate logistic regression analysis showed that a decrease in Maresin 1 concentration was still associated with osteopenia (P = 0.035) or PMOP (P = 0.016). Maresin 1 levels had a maximum area under curve of 0.820 for osteopenia and 0.746 for PMOP (P < 0.001). Our results showed that the serum Maresin 1 levels were reduced in osteopenia and PMOP patients compared with that in normal subjects, and were the lowest in the PMOP subjects. The results suggest that Maresin 1 may serve as a new non-invasive diagnostic biomarker for PMOP.